Comparison of the background echotexture between automated breast ultrasound and handheld breast ultrasound. Issue 27 (8th July 2022) - Kim, Jieun; Ko, Eun Young; Han, Boo-Kyung; Ko, Eun Sook; Choi, Ji Soo; Park, Ko Woon; Kim, Haejung
Abstract : This study aimed to compare the background echotexture (BE) between automated breast ultrasound (ABUS) and handheld breast ultrasound (HHUS) and evaluate the correlation of BE with mammographic (MG) density and background parenchymal enhancement (BPE) on magnetic resonance imaging (MRI). A total of 212 women with newly diagnosed breast cancer who had undergone preoperative ABUS, HHUS, MG, and MRI were included. Two breast radiologists blinded to the menopausal status analyzed the BE of the contralateral breasts of the patients with breast cancer in consensus. The MG density and BPE of breast MRI on the radiologic reports were compared with the BE in the ultrasound. We used the cumulative link mixed model to compare the BE and Spearman rank correlation to evaluate the association between BE with MG density and BPE. BE was more heterogeneous in ABUS than in HHUS ( P < .001) and in the premenopausal group than in the postmenopausal group ( P < .001). The heterogeneity of BE in the premenopausal group was higher with ABUS than with HHUS ( P = .013). BE and MG density showed a moderate correlation in the postmenopausal group, but a weak correlation in the premenopausal group. BE and BPE showed moderate correlations only in the premenopausal group. ABUS showed a more heterogeneous BE, especially in the premenopausal group. Therefore, more attention is required to interpret ABUS screening in premenopausal women.